The Practice Effect on Seguin Form Board Test - Rajni Raina (Journal of All India Institute of Speech and Hearing, 1970)
There have been many tests of intelligence which require motor performance. Examples  might  be  given  of  Alexander's  Pass Along Test, Object Assembly (sub-tests), Pinter-Patterson Performance Scale, Aurthur Point Scale and Seguin Form Board Test, etc. The time scores of subject are converted into I.Q. scores for purpose of interpretation of the level of intellectual functioining.  Repeated evaluation of the same subject on such tests invariably show better performance merely because of the effect of practice. Thereby the trial of the same test for purpose of re-evaluation after a short interval becomes questionable. Research work has not been done evaluating to what extent such practice may affect the results.